2014
DOI: 10.1007/s13280-014-0579-7
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with fishing and the desire to leave

Abstract: Predicting who may leave a fishery is an important consideration when designing capacity reduction programs to enhance both ecological and economic sustainability. In this paper, the relationship between satisfaction and the desire to exit a fishery is examined for the Queensland East Coast Trawl fishery. Income from fishing, and changes in income over the last 5 years, were key factors affecting overall satisfaction. Relative income per se was not a significant factor, counter to most satisfaction studies. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…In our case, both types of risk were associated to the same fishery (the alternative fishery) and, consequently, we could not distinguish them. Pascoe et al [55] analysed the exit decisions and found that satisfaction with fishing of the challenge of fishing was key on exit decisions whereas other economic variables were not significant. On the other hand, we have extended these and other previous works in the fishing sector by including the effect of other organizational variables such as separation of ownership and management, family employees or family related managers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our case, both types of risk were associated to the same fishery (the alternative fishery) and, consequently, we could not distinguish them. Pascoe et al [55] analysed the exit decisions and found that satisfaction with fishing of the challenge of fishing was key on exit decisions whereas other economic variables were not significant. On the other hand, we have extended these and other previous works in the fishing sector by including the effect of other organizational variables such as separation of ownership and management, family employees or family related managers.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on which of these two fisheries is closer to sustainable levels, it could be interesting to encourage fishermen to operate in one or another. This is a relevant issue as overcapacity in fisheries is widely accepted as a major problem at the international level [55]. A deep knowledge of the potential reactions of the fleet at the individual level could provide interesting policy implications and could also provide a hint for a better management design.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations